# Transformation of function

1. Feb 14, 2016

### hotjohn

1. The problem statement, all variables and given/known data
dy/dx = (2x +y -1) / ( 4x -2y +1) , x= X +1 , y = Y-1 ,, how to make it into differential equation ? my ans is not same as the ans given .
P/s : in the second photo , it's lnx +c , sorry for the blur photo

2. Relevant equations

3. The attempt at a solution

#### Attached Files:

File size:
20.7 KB
Views:
49
• ###### 0743.jpg
File size:
43 KB
Views:
50
2. Feb 16, 2016

### HallsofIvy

Staff Emeritus
What you give already is a differential equation! Do you mean "change from a differential equation in x and y to a differential equation in X and Y"? If you can immediately replace x and y on the right side of the equation by X+ 1 and Y- 1. For the left side, use the "chain" rule:
$$\frac{dy}{dx}= \frac{dy}{dY}\frac{dY}{dx}= \frac{dy}{dY}\frac{dY}{dX}\frac{dX}{dx}$$.

3. Feb 17, 2016

### hotjohn

in the photo posted , i have already showed that dy/ dY = 1 , dx/dX =1 , so i can conclude that dy=dY , dx=dX , so for the original dy/dx , i can make it as dY/dX , and replace the x as X+1 , and y = Y+1 , so i have dY/dX = (2X+Y) / (X+2Y)

4. Feb 17, 2016

### hotjohn

But , i still didnt get the ans

5. Feb 17, 2016

### HallsofIvy

Staff Emeritus
Well, what was the "ans given"? And are you sure you are not getting it? In your first post, you have your answer as an equation involving several logarithms. You can use the "laws of logarithms" to reduce your equation to "ln(A)= ln(B)" and then take the exponential of both sides to get "A= B".